Analysis of Kinesthetic Intelligence and Self-Confidence on The Success of Playing Egrang - Nonik Rahesti; Fajar Awang Irawan; Bambang Priyono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Egrang is a traditional Indonesian game that is important to preserve, where this game involves motor skills, balance, concentration, and social interaction. This study aims to analyze the contribution of kinesthetic intelligence and self-confidence to the success of playing egrang. This study uses a quantitative method with a regression correlation design. The sample used in this study were 51 elementary school students in Semarang Regency who had filled out inform consent as a willingness to participate in the study. The data in this study were obtained using several test instruments, namely physical tests to measure kinesthetic intelligence, concentration tests using concentration exercise grids, questionnaire tests to measure self-confidence levels, and egrang playing skills tests which then the data were processed using SPSS software version 25.0. The results showed that kinesthetic intelligence and self-confidence had a significant contribution to the success of playing egrang, with a total contribution of 49.5%. Kinesthetic intelligence and self-confidence have a close relationship in supporting the success of playing egrang. Kinesthetic intelligence provides technical ability, and self-confidence strengthens the mental courage to implement it. Future research is expected to be able to analyze and identify other factors that can contribute to the success of egrang.